Filling in the Gaps: Adopting Ultraconserved Elements Alongside COI to Strengthen Metabarcoding Studies - Pierce, Mac P. (Frontiers in Ecology and Evolution, 2019)
Metabarcoding is rapidly gaining popularity as a means of conducting biodiversity studies. Using DNA barcodes to identify and catalogue biodiversity has many advantages, and compares favorably with traditional methods based on morphological examination. Ease of use, taxonomic coverage, and increased efficiency are qualities that make metabarcoding a valuable ecological tool, particularly in light of the drastic anthropogenically induced ecosystem changes currently underway. However, limitations and challenges pertaining to existing barcodes create gaps from which inaccuracies can arise, contributing to skepticism regarding the value of metabarcoding based methods. Developing novel ways to address these limitations is crucial to improve metabarcoding methods and dispel doubt about their utility. Ultraconserved genomic elements (UCEs), genetic markers that have been used successfully in the field of phylogenomics, possess advantageous qualities that may be applied to fill in the gaps of existing metabarcoding methods. Here, I outline the strengths of UCEs and discuss their potential for complementing and strengthening existing metabarcoding methods based on the mitochondrial marker cytochrome oxidase I (COI).